AN ANALYSIS OF REFUSAL STRATEGY OF THE CHILDREN AT KETARE VILLAGE: A PRAGMATIC STUDY - Puspita Dewi; Baiq Novia Wibawa (Diglosia : Jurnal Pendidikan, Kebahasaan, dan Kesusastraan Indonesia, 2020)
The aims of this study are to identify refusal strategies used by children at Ketare village and to analyze the factors that influence the differences refusal strategies used by children at Ketare village. This study used descriptive qualitative method. The data was collected by observing, recording and taking notes. The results of this study are direct and indirect refusal strategies identified at Ketare. Related to family scope, there is direct refusal with nonperformative statements and indirect refusal with excuse, reason, explanation, set condition for future or fast acceptance, and promise of future acceptance. Related to children scope there are direct refusal with non-performative statement and indirect refusal with statement of regret, excuse reason explanation, set condition for future acceptance, and promise of future acceptance. In terms of adult’s scope, they are direct refusal with data non-performative statement. The factors of different refusal used by children are factors from gender, age, environment, and social culture.